Pendugaan Umur Simpan Mi Instan Berbasis Tepung Jagung Lokal Riau dan Tapioka Menggunakan Metode Akselerasi - Matius Teddy Ginting; Usman Pato; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study was to determine the shelf life of instant noodles made from local corn flour with or without the addition of tapioca. This study was conducted experimentally using the Accelerated Storage Studies Method by keeping the products for 28 days at temperatures of 35ºC, 45ºC, 55ºC, the observed parameter organoleptic quality and TBA values. The results showed the self life of instant noodles made with or without the addition of tapioca were 39,552 days and 49,869 days, respectively. Keywords: Corn flour, Tapioca, Shelf Life and Accelerated Methods